2011
DOI: 10.1089/jwh.2010.2275
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure to Brominated Flame Retardants and Abnormal Pap Test Results

Abstract: Objective: This study examined a possible association of dietary exposure to polybrominated biphenyls (PBBs), a brominated flame retardant, and self-reported abnormal Pap test results and cervical dysplasia as a precursor to cervical cancer. Methods: Women in Michigan who ingested contaminated poultry, beef, and dairy products in the early 1970s were enrolled in a population-based cohort study in Michigan. Serum PBB and serum polychlorinated biphenyl (PCB) concentrations were measured. Reproductive history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Studies conducted to date have not identified an association between PBB exposure and incidence of endometriosis [ 43 ] or risk of spontaneous abortion [ 44 ]. PBB exposure was also not associated with a risk of an abnormal pap test result [ 45 ]. However, these studies were all conducted in individuals that were directly exposed to PBBs.…”
Section: Effects Of Pbbs In Humansmentioning
confidence: 99%
“…Studies conducted to date have not identified an association between PBB exposure and incidence of endometriosis [ 43 ] or risk of spontaneous abortion [ 44 ]. PBB exposure was also not associated with a risk of an abnormal pap test result [ 45 ]. However, these studies were all conducted in individuals that were directly exposed to PBBs.…”
Section: Effects Of Pbbs In Humansmentioning
confidence: 99%
“…Plastic materials are used in every aspect of our lives [ 19 ] and common routes of exposure to plastic chemicals and particles [ 20 ] include inhalation [ 21 ], ingestion (including trophic transfer) [ 22 24 ] and direct dermal contact [ 25 27 ]. Furthermore, children are exposed prenatally to plastic chemicals through maternal and paternal exposure [ 28 ], as well as postnatally through breast milk [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic materials are used in every aspect of our lives (19) and common routes of exposure to plastic chemicals and particles (20) include inhalation (21), ingestion (including trophic transfer) (22)(23)(24), and direct dermal contact (25)(26)(27). Furthermore, children are exposed prenatally to plastic chemicals through maternal and paternal exposure (28), as well as postnatally through breast milk (29).…”
mentioning
confidence: 99%